2006
DOI: 10.2170/physiolsci.rp006406
|View full text |Cite
|
Sign up to set email alerts
|

Organelles Containing Inositol Trisphosphate Receptor Type 2 in Adrenal Medullary Cells

Abstract: Abstract:To identify which organelles contained inositol trisphosphate (InsP 3 ) receptor type 2 (InsP 3 R2) in adrenal medullary (AM) cells, immunocytochemical and biochemical studies were performed on AM cells of several species. InsP 3 R2-like immunoreactive materials produced by two different anti-InsP 3 R2 antibodies (Abs) (Chemicon and Sigma) were distributed in rat AM cells in agreement with BODIPY-FL-InsP 3 binding sites. For two other Abs (KM1083 and Santa Cruz), some of the antiInsP 3 R2 immunoreacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
1
6
0
3
Order By: Relevance
“…Since the punctate distribution of TRPC1 channel-like IR resembles that of the endoplasmic reticulum (ER), AM cells were double stained with the anti-TRPC1 Ab and BODIPY-FL-thapsigargin, a chemical that selectively binds to the ER (9,25). Figure 7D clearly shows that the majority of TRPC1 channel-like IR coincided with BODPY-FL thapsigargin binding (n ϭ 12), suggesting that TRPC1 channels are present in the ER in AM cells.…”
Section: Resultsmentioning
confidence: 98%
“…Since the punctate distribution of TRPC1 channel-like IR resembles that of the endoplasmic reticulum (ER), AM cells were double stained with the anti-TRPC1 Ab and BODIPY-FL-thapsigargin, a chemical that selectively binds to the ER (9,25). Figure 7D clearly shows that the majority of TRPC1 channel-like IR coincided with BODPY-FL thapsigargin binding (n ϭ 12), suggesting that TRPC1 channels are present in the ER in AM cells.…”
Section: Resultsmentioning
confidence: 98%
“…, 1996, 2006). However, results from other authors indicate that in chromaffin cells, InsP 3 receptors are present in the ER but not in the secretory granules (Endo et al. , 2006).…”
Section: Introductionmentioning
confidence: 97%
“…The reasons for the discrepancy may rely in the different properties of the different kinds of secretory granules, and perhaps also in the different methodologies for measuring granular [Ca 2? ], either in a whole population of heterogeneous granules or in defined when stimulated with InsP 3 , suggesting the presence of InsP 3 receptors in the vesicles. In fact, the presence of InsP 3 R in the membrane of chromaffin cell secretory granules has been a matter of debate for a long time (Yoo and Albanesi 1990;Pouli et al 1998;Huh et al 2005;Endo et al 2006;Yoo 2010). Regarding ryanodine receptors, we show that caffeine releases Ca 2?…”
Section: Discussionmentioning
confidence: 77%
“…Some authors have reported that chromaffin granules (Yoo and Albanesi 1990;Huh et al 2005;Yoo 2010), mast cell secretory granules (Quesada et al 2001(Quesada et al , 2003 and pancreatic acinar cells secretory granules (Gerasimenko et al 1996(Gerasimenko et al , 2006 possess functional inositol 1,4,5-trisphosphate (InsP 3 ) receptors. However, work from other authors suggests that InsP 3 receptors are present only in the endoplasmic reticulum but not in the secretory granules of chromaffin cells (Endo et al 2006), or that cell stimulation does not produce any Ca 2? release from the granules in PC12 cells (Pouli et al 1998).…”
Section: Introductionmentioning
confidence: 98%